1986
DOI: 10.1172/jci112500
|View full text |Cite
|
Sign up to set email alerts
|

Acute metabolic effects and half-lives of intravenously administered insulinlike growth factors I and II in normal and hypophysectomized rats.

Abstract: Insulinlike growth factors (IGF) act qualitatively like insulin on insulin target tissues in vitro. In the circulation in vivo they are bound to specific carrier proteins. In this form or when continuously infused into hypophysectomized (hypox) rats they do not exert acute insulinlike effects on glucose homeostasis. This study definitively shows that intravenous bolus injections of pure IGF I or II act acutely on glucose homeostasis: they lower the blood sugar, enhance the disappearance of U-['4qglucose from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
157
2
6

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(182 citation statements)
references
References 31 publications
17
157
2
6
Order By: Relevance
“…In a previous study, lipid metabolism was investigated in mouse monocytes after incubation with [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]oleate (33). Of the radioactivity associated with lipid, 80% of oleate was shown to be incorporated into triglycerides, 18% was incorporated into phospholipids, and 2% was recovered as non-esterified fatty acids.…”
Section: Effects Of Igf-i On Glut Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, lipid metabolism was investigated in mouse monocytes after incubation with [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]oleate (33). Of the radioactivity associated with lipid, 80% of oleate was shown to be incorporated into triglycerides, 18% was incorporated into phospholipids, and 2% was recovered as non-esterified fatty acids.…”
Section: Effects Of Igf-i On Glut Isoformsmentioning
confidence: 99%
“…Insulin-like growth factor-I (IGF-I) has a structural similarity to insulin (3) and its metabolic effects are considered to be similar to those of insulin (4,5). However, in contrast to insulin, IGF-I is ineffective in suppressing hepatic glucose production (6)(7)(8) and has a preferential effect to increase the rates of glycolysis in tissues such as muscle (5).…”
Section: Introductionmentioning
confidence: 99%
“…IGF-BPs were first identified as serum proteins that prolonged the half-life of the insulin-like growth factors (IGFs) (Cohen and Nissley, 1976;Kaufmann et al, 1977). The IGF-BPs extend the half-life of IGF in vitro and in vivo from a few minutes (for free IGF) to several hours (Cohen and Nissley, 1976;Zapf et al, 1986). This increase in half-life permits IGF to circulate at levels (-1 ug/ml) two to three orders of magnitude higher than most peptide hormones (Hintz, 1990).…”
Section: Regulation In Time and Spacementioning
confidence: 99%
“…Previous studies reported the half-life of free IGF-1 as around 20-30 min and the half-life of carrier protein-bound IGF-1 as 4 to 15 hr [12,13]. The biological half-life of GH is only about 20 min [14] and the GH level decreases rapidly after successful transsphenoidal adenomectomy [15].…”
Section: Discussionmentioning
confidence: 99%